Association of Clinical Events With Everolimus Exposure in Kidney Transplant Patients Receiving Low Doses of Tacrolimus. Issue 9 (4th March 2017) - Shihab, F.; Qazi, Y.; Mulgaonkar, S.; McCague, K.; Patel, D.; Peddi, V. R.; Shaffer, D.
Abstract : A key objective in the use of immunosuppression after kidney transplantation is to attain the optimal balance between efficacy and safety. In a phase 3b, multicenter, randomized, open‐label, noninferiority study, the incidences of clinical events, renal dysfunction, and adverse events (AEs) were analyzed at 12 months in 309 de novo renal transplant recipients receiving everolimus (EVR), low‐dose tacrolimus (LTac), and prednisone. Cox proportional hazard regression modeling was used to estimate the probability of clinical events at specified combinations of time‐normalized EVR and Tac trough concentrations. At 12 months, the highest incidence of treated biopsy‐proven acute rejection (tBPAR) and graft loss occurred most often in patients with EVR trough concentration <3 ng/mL (64.7% and 10.5%, respectively). At 1 month and 12 months, increasing EVR levels were associated with fewer tBPAR events (both p < 0.0001). Low estimated glomerular filtration rate (eGFR) and decreased eGFR occurred more often in patients with lower EVR and higher Tac levels. AEs were most often observed in patients with EVR levels <3 ng/mL. This study supports maintaining an EVR trough concentration of 3–8 ng/mL, when combined with LTac, to achieve balanced efficacy and safety in renal transplant recipients. Trial registration: NCT01025817. Abstract : This post hoc exploratory analysis of the US92 study assesses efficacy and safety events with specific everolimus and tacrolimus trough concentrations, and supports maintaining an everolimus trough concentration of 3–8 ng/mL when combined with low‐dose tacrolimus to achieve favorable efficacy and safety outcomes in renal transplant patients.